ANALISIS PERBANDINGAN KINERJA SISTEM DISTRIBUSI PANAS PADA VARIASI RUANG MESIN PENGERING IKAN - Ahmad Aryadillah; Aqli Mursadin (Scientific Journal of Mechanical Engineering Kinematika, 2016)
The purpose of this research is to know the heat distribution system in three types of fish dryers. The variations of the dryer room were fire-tube type, fire-tube type with bevel, and air-tube type. This study was conducted by simulating airflow and heat transfer that occurred in each dryer room variation by using CFD software. In the simulation, the dryer was heated using an electric heating element with a temperature of 80 Â°C and the results display hot air flow moving in the drying chamber. In the fire-tube type dryer room obtained average temperature of 46.74OC. In the fire-tube type dryer room with the bevel obtained an average temperature of 44.40OC. While the type of air-tube shows average temperature results of 34.31OC. From the simulation, we known that the fire-tube type has the best heat distribution system.